2021
DOI: 10.1080/13696998.2021.1942017
|View full text |Cite
|
Sign up to set email alerts
|

Budget impact of tepotinib in the treatment of adult patients with metastatic non-small cell lung cancer harboring METex14 skipping alterations in the United States

Abstract: Budget impact of tepotinib in the treatment of adult patients with metastatic non-small cell lung cancer harboring METex14 skipping alterations in the United States

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…65 More information about annual drug costs is provided in Appendix Tables 1 and 2 in Supplemental Materials found at https://doi.org/10.1016/j.jval.2023.08.010 . Healthcare resources for disease management in the pre- and post-progression states were based on Stargardter et al 58 (see Appendix Tables 3 and 4 in Supplemental Materials found at https://doi.org/10.1016/j.jval.2023.08.010 ). The frequency of healthcare resource use was assumed the same for all therapies and subgroups.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…65 More information about annual drug costs is provided in Appendix Tables 1 and 2 in Supplemental Materials found at https://doi.org/10.1016/j.jval.2023.08.010 . Healthcare resources for disease management in the pre- and post-progression states were based on Stargardter et al 58 (see Appendix Tables 3 and 4 in Supplemental Materials found at https://doi.org/10.1016/j.jval.2023.08.010 ). The frequency of healthcare resource use was assumed the same for all therapies and subgroups.…”
Section: Methodsmentioning
confidence: 99%
“… 57 Separate estimates were used for Medicare and commercial payer perspectives. Costs from a Medicare perspective associated with intravenous drug administration and disease management were calculated based on the resource use 58 multiplied by unit cost obtained from the Centers for Medicare & Medicaid Services 2022 fee schedule. 66 Costs from a commercial payer perspective were based on a prior study.…”
Section: Methodsmentioning
confidence: 99%
“…Most of the included studies originated in the United States (n = 18, 62%) (42-46, 48, 50-59, 64, 66), followed by Italy (n = 2, 7%) (69,70) and one from each of Brazil (60), the Netherlands (62), France (47), Japan (49), Norway (65), Saudi Arabia (61), Spain (63), and Thailand (67), as well as one multi-country study (58). The studies covered 11 types of cancer including non-small-cell lung cancer (n =8, 28%) (43,45,47,54,55,57,62,65), prostate cancer (n =5, 17%) (42,44,48,59,64), colorectal cancer (n = 4, 14%) (60,67,68,70), ovarian cancer (n = 3, 10%) (46,53,63), breast cancer (n = 2, 7%) (56,61), myeloma (n = 2, 7%) (49,58), melanoma (n = 1, 3%) (52), head and neck cancer (n = 1, 3%) (69), cell carcinoma of the urothelium (n = 1, 3%) (50), gastroenteropancreatic neuroendocrine tumor (n = 1, 3%) (66), and epithelial ovarian, fallopian tube or primary peritoneal cancer (n = 1, 3%) (51). Most of the interventions in these studies involved innovative anticancer drugs, including selective poly ADP-ribose polymerase (PARP)-1 and PARP-2 inhibitor (e.g., niraparib) (51,53), epidermal growth factor receptor (EGFR) and human epidermal growth factor receptor 2 tyrosine kinases inhibitor (e.g., afatinib) (55,…”
Section: Systematic Reviewmentioning
confidence: 99%
“…Regarding the perspective, three studies (10%) considered the societal perspective (57,67,69), four studies (14%) considered the healthcare system perspective (60,62,63,70), and all other studies (n = 22, 76%) considered the budget-holder perspective (42-56, 58, 59, 61, 64-66, 68). Regarding the budget-holder perspective, one study calculated the budget impact from the hospital perspective (66), five adopted the health-plan perspective (45,46,48,55,64), and 16 adopted the third-party payer perspective including public health insurance, Medicare, and commercial insurance (42-44, 47-54, 56, 58, 59, 61, 65, 68). Five studies reported results from more than one perspective (43,50,54,58,68).…”
Section: Systematic Reviewmentioning
confidence: 99%
See 1 more Smart Citation